Ćarkić М. Ž. On Poetic Language - Васько, P.; Радзієвська, Т. (Мовознавство, 2011)
Рецензія на книгу: Čarkić M. Ž. On Poetic Language. Belgrade : Institute of the Serbian Language, Serbian Academy of Sciences and Arts, 2010.— 245 p.